"Introduction" in Challenges and Opportunities for Eurozone Governance - Caetano, José Manuel (2019)
The recent global financial crisis and its impacts on the Eurozone have been the subject of many studies, mostly emphasizing the economic dimension. However, the different patterns of responses to the crisis delivered by countries and institutions reflect very distinct political stands. Hence, in order to better grasp the crisis complexity, a multidisciplinary approach, involving the perspectives of both economics and political science, is required. For a broad and coherent vision of the Eurozone crisis and of the exposed limitations of its governance model, one should use the lens of economic analysis on the interfaces of the various interconnected macroeconomic variables. But one should also take into account the features related to decision making processes and resource allocation in a multilevel governance framework, which the crisis has highlighted and has put on the international agenda. With such a mindset, the focus of this book is on the Mundellian rationale of optimal currency areas and its interaction with the Maastricht Treaty institutional framework, which supports the European Monetary Union building. On the other hand, structural vacuums in the regulatory design of the Eurozone have been accompanied by a manifest lack of effective political leadership in the EU’s reactions to the crisis, weakening the credibility and reputation of the single currency and leaving Member States dramatically exposed to the logic of global financial markets. The crisis was a crucial event in the European integration process and its developments will permanently sway the future of the European Union. It is therefore not surprising that, faced with the lacunae in the governance of the Eurozone and the coordination failures of its political reactions, the community institutions have looked for better ways to improve the sustainability of the Eurozone design. Such alternatives are profusely discussed in this book. However, in spite of many meritorious efforts, relevant challenges still remain and must be faced for the sake of a more resilient EMU, namely: the completion of the banking union, which is aimed at strengthening the integrity of the euro and the risk sharing capacity of banks and sovereigns; a better coordination of fiscal policies, to reinforce the stabilization role at the central level; and the promotion of structural reforms, to shape an efficient and stable EMU, capable of generating and distributing wealth. This book discusses and proposes responses to the challenges of devising viable governance, oriented to the progressive reduction and sharing of risks, in a more European oriented perspective, in which central and peripheral countries find their ways to prosperity. The book incorporates views of economists and political scientists who revisit and reflect on the causes of the crisis and on its socio-economic effects. The latest changes to the Eurozone governance model are cross-examined along with prospective analyses of some milestones that still need to be achieved. The recent global financial crisis and its impacts on the Eurozone have been the subject of many studies, mostly emphasizing the economic dimension. However, the different patterns of responses to the crisis delivered by countries and institutions reflect very distinct political stands. Hence, in order to better grasp the crisis complexity, a multidisciplinary approach, involving the perspectives of both economics and political science, is required. For a broad and coherent vision of the Eurozone crisis and of the exposed limitations of its governance model, one should use the lens of economic analysis on the interfaces of the various interconnected macroeconomic variables. But one should also take into account the features related to decision making processes and resource allocation in a multilevel governance framework, which the crisis has highlighted and has put on the international agenda. With such a mindset, the focus of this book is on the Mundellian rationale of optimal currency areas and its interaction with the Maastricht Treaty institutional framework, which supports the European Monetary Union building. On the other hand, structural vacuums in the regulatory design of the Eurozone have been accompanied by a manifest lack of effective political leadership in the EU’s reactions to the crisis, weakening the credibility and reputation of the single currency and leaving Member States dramatically exposed to the logic of global financial markets. The crisis was a crucial event in the European integration process and its developments will permanently sway the future of the European Union. It is therefore not surprising that, faced with the lacunae in the governance of the Eurozone and the coordination failures of its political reactions, the community institutions have looked for better ways to improve the sustainability of the Eurozone design. Such alternatives are profusely discussed in this book. However, in spite of many meritorious efforts, relevant challenges still remain and must be faced for the sake of a more resilient EMU, namely: the completion of the banking union, which is aimed at strengthening the integrity of the euro and the risk sharing capacity of banks and sovereigns; a better coordination of fiscal policies, to reinforce the stabilization role at the central level; and the promotion of structural reforms, to shape an efficient and stable EMU, capable of generating and distributing wealth. This book discusses and proposes responses to the challenges of devising viable governance, oriented to the progressive reduction and sharing of risks, in a more European oriented perspective, in which central and peripheral countries find their ways to prosperity. The book incorporates views of economists and political scientists who revisit and reflect on the causes of the crisis and on its socio-economic effects. The latest changes to the Eurozone governance model are cross-examined along with prospective analyses of some milestones that still need to be achieved.